Zagadnienie nawrócenia i pokuty w dziełach Sulpicjusza Sewera - Józef Pochwat (Polonia Sacra)
In his writings, Sulpicius Severus (360–420) urged his readers to repentance, so they would not expose themselves to eternal damnation, and therefore not remain in a state of slavery in this life. When a lawyer from Bordeaux encourages penance, He pays special attention to the fact that sin calls for the right punishment. Despite this, Sulpicius is a man full of Christian optimism and he emphasizes mercy that God only offers to those people who admit their sins and undertake an appropriate penance.